READING, AS ONE OF KEY FACTORS FOR HUMAN PROGRESS - Fotima Matmusayeva (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
Many individuals often face to trouble with reading. Reading well takes a while, persistence, and training! The most significant matter to figure out is the purpose of your reading: looking at directions to build a toy house and reading a textbook are not the same thing. At the university, students have to deal with a heavy load of reading materials, often involving tough subjects and terms. Therefore, students need to brush up on their reading comprehension skills. This article discusses the importance of reading as a skill and suggests some reading strategies for students.